Description and characterization of a penicillin-resistant Streptococcus dysgalactiae subsp. equisimilis clone isolated from blood in three epidemiologically linked patients. (1st September 2016) - Fuursted, Kurt; Stegger, Marc; Hoffmann, Steen; Lambertsen, Lotte; Andersen, Paal Skytt; Deleuran, Mette; Thomsen, Marianne Kragh
Abstract : Background: During a 27 month period, we detected four incidents of penicillin-resistant (PR) Streptococcus dysgalactiae subsp. equisimilis (SDSE) isolated from blood cultures of three patients. Methods: The 4 PR-SDSE were compared phenotypically and molecularly (using WGS) with 36 penicillin-susceptible SDSE from blood cultures obtained in the same catchment area and time period. Results: Phylogenetic analysis showed that the four PR-SDSE belonged to a single clone and a possible epidemiological link between the three patients was identified to be a dermatology department. MICs of penicillin were determined to be 0.5–2 mg/L using Etest and 0.5 mg/L when tested by a broth microdilution method. The four PR-SDSE were unrelated to the 36 penicillin-susceptible isolates, which could suggest that they did not evolve locally from a susceptible clone, but have been introduced into the region. In silico genome-based resistome analysis revealed identical PBP mutations in all four isolates. We detected mutations in multiple PBPs, including two amino acid substitutions within the active sites of the transpeptidase domain of PBP2x (T341P and Q555E), which have also been detected in other PR streptococci. The remaining mutations were, however, all located outside the active-site motifs of the transpeptidase domain. Conclusions: To the best of our knowledge, this is the first description and characterization of invasive PR-SDSE. The resistant isolates had several amino acid changes in various PBPs compared with penicillin-susceptible SDSE. The observation that SDSE also can become PR emphasizes the importance of performing antimicrobial susceptibility testing.